African Elephant Specialist Group report - Holly Dublin (Pachyderm)
This report serves as a programme review noting: the major points of discussion at the fifth AfESG Meeting, January 28 - February 1, 2002, in Shaba NR, Kenya; the integration of data and future of analysis and presentation as suggested by the Data Review Task Force which met November 30 - December 2, in Naivasha, Kenya; the situation vis a vis the implementation of MIKE; and the ongoing work implemented under the aegis of the Human-Elephant Conflict Task Force (now Working Group) which deals with both the training of managers involved in conflict mitigation and the mapping of conflict areas. Responsibilities undertaken by the Programme Officers in the West and Central African offices, improvements of the AfESG web site, and requests of assistance in possible elephant relocation in Senegal-Burkina Faso which prodded the establishment of the Reintroduction Task Force (RTF) which is working on recommendations and guidelines for such programmes are also discuss.